2021
DOI: 10.1177/21925682211034845
|View full text |Cite
|
Sign up to set email alerts
|

CT Osteoabsorptiometry Assessment of Subchondral Bone Density Predicts Intervertebral Implant Subsidence in a Human ACDF Cadaver Model

Abstract: Study Design: Cadaveric biomechanics study. Objective: Subchondral bone mineral density (sBMD) reflects the long-term mineralization and distribution of stress on joints. The use of 3-dimensional (3-D) methods to evaluate sBMD, including computed tomography osteoabsorptiometry (CT-OAM), enables the assessment of density distribution with emphasis on subchondral bone. This study sought to measure the sBMD of cervical endplates using CT-OAM and correlate it to mechanical implant subsidence in a cadaveric model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Therefore, non-destructive measurement of subchondral bone density provides a realistic estimate of the endplate's strength. Recent human studies have also shown that higher sBMD in the endplates is associated with a lower likelihood of subsidence compared to endplates with lower sBMD and vice versa [21,33]. This further validates the use of CT-OAM as a valuable tool for predicting cage subsidence and optimization of cage design based on CT-OAM bone density mapping like in human spinal surgery [34].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, non-destructive measurement of subchondral bone density provides a realistic estimate of the endplate's strength. Recent human studies have also shown that higher sBMD in the endplates is associated with a lower likelihood of subsidence compared to endplates with lower sBMD and vice versa [21,33]. This further validates the use of CT-OAM as a valuable tool for predicting cage subsidence and optimization of cage design based on CT-OAM bone density mapping like in human spinal surgery [34].…”
Section: Discussionsupporting
confidence: 56%
“…Typically, CT-OAM values are expressed in Hounsfield Units (HU). The distribution of bone mineral density in the vertebral endplates assessed using CT-OAM has been strongly correlated with the local mechanical strength of the endplates in humans, as determined by indentation testing [21][22][23][24][25]. Reversely, by mapping the subchondral bone density of the endplates, we gained direct insights into their mechanical strength and the potential implications for cage design.…”
Section: Introductionmentioning
confidence: 96%
“…Past studies have demonstrated that the central endplate represent the region of lowest subchondral BMD and is thus less resistant to compressive load than the peripheral endplate. [18][19][20][21] A biomechanical study evaluating the effect of cage width in a human cadaveric lateral lumbar interbody fusion (LLIF) model found that placement of a larger cage that spans the width of the ring apophysis increased the compressive strength of the construct, thus decreasing the risk of subsidence. 22 Few clinical studies have investigated the relationship between cage placement and subsidence in posterior approaches to lumbar fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between BMD and endplate strength has been well established, with several biomechanical studies demonstrating a higher risk of endplate failure with lower BMD due to lower compressive strength under dynamic loading. [19][20][21]25 Clinical studies have also found low BMD and osteoporosis to significantly increase the risk for subsidence in the context of several fusion procedures, including LLIF, posterior lumbar interbody fusion (PLIF), and transforaminal lumbar interbody fusion (TLIF). 10,[26][27][28] Recently, a study by Jones et al used QCT technology to assess how the BMD of the cage footprint affected the risk for subsidence in LLIF, establishing a cutoff for volumetric trabecular BMD of 211.04 kg/m 2 , below which risk for subsidence was increased.…”
Section: Discussionmentioning
confidence: 99%
“…High mechanical strength was substantially linked with high density regions of the acetabulum and femoral head (SBP correlation coefficients ranged from 0.77 to 0.97 for FL and 0.97 to 0.96 for CF) ( Hoechel et al, 2013 ). Several researchers have discovered a link between the density distribution and mechanical strength of the talar dome ( Leumann et al, 2015 ), cervical vertebral body ( Hara et al, 2021 ), and upper and lower cervical endplate ( Orías et al, 2021 ). Yet, we are aware that, while there is a strong association between the two in this sort of research, a quantitative comparison of bone density and mechanical strength is unachievable.…”
Section: Correlation Between Bone Density and Mechanical Strengthmentioning
confidence: 99%